American College of Sports Medicine position stand. Exercise and fluid replacement - Sawka, M. N.; Burke, L. M.; Eichner, E. R.; Maughan, R. J.; Montain, S. J.; Stachenfeld, N. S. (Medicine & Science in Sports & Exercise, 2007)
This Position Stand provides guidance on fluid replacement to sustain appropriate hydration of individuals performing physical activity. The goal of prehydrating is to start the activity euhydrated and with normal plasma electrolyte levels. Prehydrating with beverages, in addition to normal meals and fluid intake, should be initiated when needed at least several hours before the activity to enable fluid absorption and allow urine output to return to normal levels. The goal of drinking during exercise is to prevent excessive (>2% body weight loss from water deficit) dehydration and excessive changes in electrolyte balance to avert compromised performance. Because there is considerable variability in sweating rates and sweat electrolyte content between individuals, customized fluid replacement programs are recommended. Individual sweat rates can be estimated by measuring body weight before and after exercise. During exercise, consuming beverages containing electrolytes and carbohydrates can provide benefits over water alone under certain circumstances. After exercise, the goal is to replace any fluid electrolyte deficit. The speed with which rehydration is needed and the magnitude of fluid electrolyte deficits will determine if an aggressive replacement program is merited. This Position Stand replaces the 1996 Position Stand "Exercise and Fluid Replacement," Med. Sci. Sports Exerc. 28(1):i-vii, 1996.